Casson nanofluid convection in an internally heated layer. (2020) - Gupta, Urvashi; Sharma, Jyoti; Devi, Mamta
Abstract: The convective instability of blood in the presence of nanoparticles has key role in medical field thereby improving the health care practices. The paper investigates the impact of nanoparticles on the onset of convection currents in blood using Casson fluid model. The fluid layer is also considered to be internally heated due to the possibility of chemical reactions in blood. The conservations equations are solved with more practical boundary conditions (rigid-free). The problem is solved analytically using normal modes and obtained results are also validated. Stability curves are drawn to explore the impact of various parameters using the software Mathematica. It is found that the nanoparticles, internal heat source and Casson parameters make the fluid less stable which establishes the enhancement in convective instability of the Casson nanofluids.